Rapid and Complete Conversion of CH3NH3PbI3 for Perovskite/C60 Planar‐Heterojunction Solar Cells by Two‐Step Deposition. Issue 5 (16th February 2017) - Sun, Weihai; Li, Yunlong; Yan, Weibo; Peng, Haitao; Ye, Senyun; Rao, Haixia; Zhao, Ziran; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : In the present work, we proposed an improved two‐step deposition method by optimizing the reaction temperature and the dipping time for the fabrication of perovskite films. The perovskite film fabricated at 70 C exhibits a full surface coverage and a smooth uniform crystal morphology with a particle size up to micrometer scale. The corresponding inverted perovskite solar cell with a structure of ITO/poly(3, 4‐ethylenedioxythiophene): poly(styrene‐sulfonate)(PEDOT:PSS)/CH3 NH3 PbI3 /C60 /2, 9‐dimethyl‐4, 7‐diphenyl‐1, 10‐phenanthroline (BCP)/Ag displayed a higher power conversion efficiency (PCE) of 13.6% than that of the device fabricated at 20 C (8.06%), as well as the high reproducibility. The small but meaningful modification for two‐step deposition would provide an efficient and convenient way to optimize planar perovskite solar cells and facilitate the potential applications of perovskite solar cells more widely. Abstract : An improved two‐step deposition method by optimizing the reaction temperature and the dipping time was proposed for the fabrication of perovskite films. The perovskite film fabricated at 70 C exhibited a full surface coverage with an average thickness of approximately 240 nm. The corresponding inverted perovskite solar cell with a structure of ITO/PEDOT PSS/CH3 NH3 PbI3 /C60 /BCP/Ag showed a superior PCE of 13.6% than those of the devices fabricated by one‐step spin‐coating method (5.73%) and two‐step deposition method at 20 C (8.06%).